PENGARUH PENAMBAHAN PROSENTASE ETHANOL DAN MODIFIKASI JENIS PISTON TERHADAP UNJUK KERJA MESIN SATU SILINDER - Bambang Junipitoyo; Moh. Fahmi Almansyah; Rifdian I.S; Bayu Dwi Cahyo (Jurnal Penelitian)
In recent years, the world's need for fossil energy such as oil and gas will increase. Meanwhile, fossil energy reserves are decreasing. This is also due to the high number of motorized vehicles. With the growth of motorized vehicles as a mode of transportation and limited fossil fuels, it is necessary to develop renewable energy as an alternative energy. This is a step to reduce the use of fossil fuels. . Ethanol is an alternative fuel source derived from plants or vegetable sources. The high octane contained in ethanol can be used as a fuel mixture or as the fuel itself. This research was carried out experimentally to determine the effect of using ethanol on the power, torque, and efficiency of the engine. In carrying out this research the first steps required are fuel, ethanol, piston variations and a tool to obtain data, namely the Dynotest. The engine will observe changes in the aspects of power, torque and efficiency by using the addition of ethanol to pertalite and piston changes. The percentages used are 25%, 30%, 35%, 40%. The results of this study obtained the best Power, Torque and Fuel Efficiency which were obtained in tests of standard piston engines and piston changes and a mixture of ethanol and pertalite obtained when using piston changes with a compression ratio of 11: 1 with a maximum power of 8.15 HP, torque at 22.96 Nm and the best fuel efficiency is 0.235 ml/s.